Feasibility of local manufacturer of spares for fertilizer factories of Bangladesh-a case study - Amin, A. K. M. Nurul; Ihsanul Karim , Syed Md. (1990)
Fertilizer factories in Bangladesh depend almost entirely on imported spare parts, which are very costly, involve foreign currency consumption and long lead time for procurement. This leads to huge inventory costs and lot of spares are kept in reserve in the fear of factory shut downs. As an attempt to solve this problem the present project work was under taken. The main objective of' the work was to conduct a feasibility study of critical spare manufacture within the country, which can save a lot of foreign exchange and ensure timely supply of spares and can bring down the factory overhead costs. Tilting pad journal bearing - a critical spare part, which has high usage value and is feasible to manufacture within the country, was selected for investigation. The material composition of selected part was identified by X-ray test, microstructure and microhardness tests. Suitable materials were chosen for the selected spare part to be made locally. Detail drawings of the part were made and manufacturing process was also developed. The part was manufactured using the technical facilities of BUET and BITAC. The produced spare was checked for quality standards and was found within acceptable limits. Economic analysis was made to evaluate the viability of manufacturing the spare part locally and it was found that an annual saving of foreign exchange of Tk. 14,00,000 will be facilitated from this particular type of bearing alone. If other size dimensions are included the saving would be much more. Net economy deserved from local manufacture of this very part is Tk. 13,56,000 per year. So it was concluded that local manufacture of Tilting pad journal bearing and other similar spares is feasible.